Sexual and Reproductive Health of Rohingya Refugee People In Bangladesh: A Systematic Review Protocol - Muhammad Anwar Hossain; Shailendra Sawleshwarkar; Iryna Zablotska-Manos (Women, Midwives and Midwifery, 2023)
Background and Objective: Rohingya refugees are one of the most vulnerable population groups from any perspective, and that certainly includes their sexual and reproductive health and access to appropriate services. This review synthesizes SRH status and needs of Rohingya women of reproductive age, addressing their experiences in accessing services. Methods: Following PRISMA guidelines, this review employs quality assessment tools (Newcastle-Ottawa Scale, MMAT, Cochrane Risk of Bias). The search strategy will be comprehensive, spanning prominent databases such as PubMed, CINAHL, Embase, Web of Science, and Scopus. Additionally, a diligent search will extend to gray literature, reference lists, and citations. Synthesis: Employing a narrative synthesis approach, the data synthesis will encompass three critical domains: the SRH status and needs of Rohingya women, the barriers encountered in accessing SRH services, and the effectiveness of existing SRH interventions. Results: The review seeks to provide valuable insights for policymakers and healthcare practitioners, offering a foundation for evidence-based strategies aimed at advancing SRH outcomes among Rohingya refugees in Bangladesh and similar Asian contexts. The review is registered in PROSPERO (CRD42023444386) for transparency and efficiency. Conclusion: Have been made to address the health and humanitarian needs of Rohingya refugees in Bangladesh, there is still limited knowledge about their SRH.